(untitled) (Economics and region, 2024)
This scientific article defines and characterizes the importance of forming and implementing the logistics strategy of an enterprise based on the stakeholders’ concept. This topic also needs more in-depth research in the context of the state of war in Ukraine, which causes the need for domestic enterprises to use new approaches to the development and implementation of a logistics strategy based on the concept of stakeholders. The research found that the influence of stakeholders on the process of managing the enterprise’s strategy, on its logistics activities, as well as on the style and methods of management, corporate culture is extremely powerful. In addition, it has been found that stakeholders can influence the resolution of strategic logistics issues related to the processes of selecting suppliers, developing or improving logistics routes, warehouse management methods, applying new logistics technologies or innovations, as well as strategic decisions on financing and quality standards, etc. To substantiate the importance of logistics, the situation that has developed in Ukraine since February 24, 2022 is considered. It is proved that under martial law, it is especially important to strengthen partnerships with the government and international partners, since this affects not only the strategic development and financial stability of the enterprise, but also the state of the national economy. The key to success was the speed of logistics decision-making and a correctly adjusted logistics strategy, which allowed enterprises to adjust internal logistics to new conditions of existence. The list of such enterprises can include LLC "BURAT-AGRO" - a multi-branch enterprise that specializes in crop production, namely in the cultivation of grain and technical crops. In addition, the implementation of a monitoring system will help the enterprise to timely identify new initiatives, changes in legislation or various programs that may affect its economic activity. It is argued that automation and digitalization of logistics reduces the level of logistics costs, increases production efficiency and labor productivity.